Assuring Potato Tuber Quality during Storage: A Future Perspective - Alamar, M. C.; Tosetti, Roberta; Landahl, Sandra; Bermejo, Antonio; Terry, Leon A. (Frontiers in Plant Science, 2017)
Potatoes represent an important staple food crop across the planet. Yet, to maintain tuber quality and extend availability, there is a necessity to store tubers for long periods often using industrial-scale facilities. In this context, preserving potato quality is pivotal for the seed, fresh and processing sectors. The industry has always innovated and invested in improved postharvest storage. However, the pace of technological change has and will continue to increase. For instance, more stringent legislation and changing consumer attitudes have driven renewed interest in creating alternative or complementary postharvest treatments to traditional chemically-reliant sprout suppression and disease control. Herein, the current knowledge on biochemical factors governing dormancy, the use of CIPC as well as existing and chemical alternatives, and the effects of pre- and postharvest factors to assure potato tuber quality is reviewed. Additionally, the role of genomics as a future approach to potato quality improvement is discussed. Critically, a better mechanistic understanding of how the pre-harvest environment influences tuber quality and the factors which govern dormancy transition should lead to a paradigm shift in how sustainable storage can be achieved.